Thermal conductivity of lightweight concrete with admixtures - Adam Hussary, Ahmad (Universiti Malaysia Sarawak, UNIMAS, 2009)
This research presents an investigation of a new lightweight concrete for construction materials which composed of cement, sand, expanded polystyrene, and wastage materials such as fly ash, silica fume, rice husk and sawdust which react as admixtures in the mix proportion. Thermal conductivity and density of the samples will be investigated. Thermal conductivity is a measure of the effectivity of the material in transmitting heat through it. The result obtained shows that the thermal conductivity value reduces with the increment addition of wastage materials in the lightweight concrete mix proportion. The wastages satisfy the basic requirement of insulation for construction materials and could be used for wall, slab and roof. Hence, with this finding it shows that it has good potential for development progress for low cost construction. Finally, apart of being a good insulation materials which save energy consumption for the building, this research also has provide an alternative to reused the wastage from the industries in order to reduce the rate of pollution.